Ganesha along with his consorts in Ganesha Mandapa - Temples of India Project Team (Jio Institute, 2024)
Within this open mandapa (pillared hall), there is a stele that depicts a figure of Ganesha along with his consorts. Ganesha is depicted standing inside a curved-roof pavilion. This depiction of Ganesha has four arms and holds his consorts on either side with his back hands, and in his front hand, he holds an akshamala (rosary). His front right hand is extended, pointing towards the ground. One of his consorts is depicted holding a modak (stuffed sweet), while the other is holding Ganesha’s hand.